(3TQM HOjYjI Uaj GdOjf GdMdHis - (3YHO GdYRjR Hf SQGjG Hf Ydj Hf CHj GdbGSe GdSfHSj GdWGFj GdMdj , Uaj GdOjf,J (B750 (3g` s
(3ChdgG (B:s
(3GeG HYO , aEf GdYdhe HGdJbOe hCLOQgG HGdEbJHGS hGdJYdje HYO eYQaI Gdg GdYXje , heYQaI MbGFb cdGe GdcQje s
(3BNQgG (B:s
(3gh BNQ eG Ufa ai YUQi hGcKQ gPg GdcJH ehLhOg YfOi hJNda YfOi ZjQgG de CNWQ Edi eWGdYJg dbdI CTJgGQg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3HChdgG hBNQgG bQGAGJ SfI (B1007 (3g`s
1030 (3hHBNQ UaMGJgG JYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B141 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B247 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B582s
Keywords: (3GdCOHs